On the information content of credit ratings and market-based measures of default risk - Gredil, Oleg R.; Kapadia, Nishad; Lee, Jung Hoon (Journal of Financial Economics, 2022)
We examine the ability of ratings and market-based measures to predict defaults. Although market-based measures are more accurate at horizons up to one year, ratings complement market-based measures and are not redundant in predicting defaults across horizons. Market-based measures differ from ratings in that they respond to both cash-flow and discount-rate news, while ratings respond primarily to cash-flow news, which is more informative of future defaults. Ratings ignore transitory shocks to credit risk, while market-based measures do not. Rating agencies respond to transitory shocks with watches rather than downgrades. Ratings are more informative during expansions and for speculative grade firms.